2018
DOI: 10.1186/s12881-018-0626-5
|View full text |Cite
|
Sign up to set email alerts
|

The altered activity of P53 signaling pathway by STK11 gene mutations and its cancer phenotype in Peutz-Jeghers syndrome

Abstract: BackgroundPeutz-Jeghers syndrome (PJS) is caused by mutations in serine/threonine kinase 11 (STK11) gene. The increased cancer risk has been connected to P53 pathway.MethodsPJS probands with STK11 mutation were included in the function analysis. P53 activity elevated by STK11 mutants was investigated using dual-luciferase reporter assay in vitro after constructing expression vectors of STK11 wild type and mutants generated by site-directed substitution. The association between the P53 activity and clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
11
0
2
Order By: Relevance
“…STK11 protein comes into play by participating in several pathways. For example, we noticed that impaired P53 activity caused by STK11 mutations in PJS patients is significantly related to cancer risk [12]. Multiplex ligation–dependent probe amplification (MLPA) together with direct sequencing raise the mutation detection rate to over 60% in most instances [13].…”
Section: Discussionmentioning
confidence: 99%
“…STK11 protein comes into play by participating in several pathways. For example, we noticed that impaired P53 activity caused by STK11 mutations in PJS patients is significantly related to cancer risk [12]. Multiplex ligation–dependent probe amplification (MLPA) together with direct sequencing raise the mutation detection rate to over 60% in most instances [13].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the LOH of STK11 or LKB1 gene is common in PJS polyps and carcinoma. A group of researchers found that abnormal p53 activity caused by a STK11 mutation leads to protein truncation and increases the risk of cancer in patients with PJS 60 . Another group showed that a possible mechanism of LKB1 inactivation resulting in colorectal malignancy led to centromere defects and genome instability via the p53‐dependent upregulation of survivin 61 …”
Section: Possible Mechanisms In the Development Of Malignancymentioning
confidence: 99%
“…However, further research findings by two-research groups revealed the involvement of LKB1 (liver kinase B1) gene mutation (also recognised as STK11 [serine/threonine kinase 11] gene) on expression of mucocutaneous melanosis. A 30%-70% of PJS sporadic cases associated with STK11/LKB1 gene mutation, however, the rate of spontaneous mutation in mucocutaneous melanosis is under investigation 9,10 . The main setback in identification of STK11/LKB1 gene in mucocutaneous melanosis patients is genetic mosaicism, lack of effective molecular techniques PJS loci, etc.. Later some studies on PJS revealed the link of loci on chromosome 16q and19q for expression of mucocutaneous melanosis.…”
Section: Genetic Defects In Peutz-jeghers Syndromementioning
confidence: 99%